Early Depletion of Primordial Germ Cells in Zebrafish Promotes Testis Formation - Keh-Weei Tzung; Rie Goto; Jolly M. Saju; Rajini Sreenivasan; Taiju Saito; Katsutoshi Arai; Etsuro Yamaha; Mohammad Sorowar Hossain; Meredith E.K. Calvert; László Orbán (Stem Cell Reports, 2015)
Summary: As complete absence of germ cells leads to sterile males in zebrafish, we explored the relationship between primordial germ cell (PGC) number and sexual development. Our results revealed dimorphic proliferation of PGCs in the early zebrafish larvae, marking the beginning of sexual differentiation. We applied morpholino-based gene knockdown and cell transplantation strategies to demonstrate that a threshold number of PGCs is required for the stability of ovarian fate. Using histology and transcriptomic analyses, we determined that zebrafish gonads are in a meiotic ovarian stage at 14 days postfertilization and identified signaling pathways supporting meiotic oocyte differentiation and eventual female fate. The development of PGC-depleted gonads appears to be restrained and delayed, suggesting that PGC number may directly regulate the variability and length of gonadal transformation and testicular differentiation in zebrafish. We propose that gonadal transformation may function as a developmental buffering mechanism to ensure the reproductive outcome. : In this article, Orban, Tzung, and colleagues report that the number of primordial germ cells (PGCs) plays a regulatory role during sexual differentiation in zebrafish. Partial depletion of PGCs leads to male bias, and a threshold number is required for ovarian development. They further provide evidence suggesting that the PGC-depleted gonads might undergo a less pronounced gonadal transformation than WTs.